Pengaruh Pelatihan Deteksi Dini Stroke dengan Metode Fast bagi Kader di Desa Nania Kecamatan Baguala Kota Ambon - Leddy Dyland Hyzkia Pattinasarany (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The frequency of strokes is increasing, with World Health Organization (WHO) data showing that around 15 million people suffer strokes every year. From the increase in the incidence of stroke above, death and disability due to stroke are still the biggest problems from year to year. Stroke can be prevented by early detection of stroke. This research aims to determine the effect of early stroke detection training using the fast method for cadres in Nania Village, Baguala District, Ambon City.This type of research is quantitative research. This research uses a quasi-experiment research design with a pre-post test control group design. Researchers provided an explanation to respondents about the FAST Act for early detection of signs of stroke. The sample in this study was 30 health cadres in the working area of ​​the Nania Community Health Center.The research results of the Pre Test knowledge scores were (10, 12 and 13) out of the highest total score of 20, the lowest score was 8 for 1 person (3.3%) and the highest score was 15 for 1 person (3.3%). Meanwhile, the Post Test Knowledge (17 and 18) of the highest total score was 20. The lowest score was 14, amounting to 1 person (3.3%), and the highest score was 20, amounting to 4 people (13.3%).The conclusion is that there is an influence of early stroke detection training using fast methods for cadres at the Nania Community Health Center, Baguala District, Ambon City. It is hoped that the research results will provide additional knowledge for medical personnel about the importance of preventing complications in diabetes sufferers, so that as much as possible we can help reduce the rate of death or disability in stroke patients.